Saikosaponin A enhances Docetaxel efficacy by selectively inducing death of dormant prostate cancer cells through excessive autophagy. (1st February 2023) - Feng, Jiling; Xi, Zhichao; Jiang, Xue; Li, Yang; Nik Nabil, Wan Najbah; Liu, Mengfan; Song, Zejia; Chen, Xiaoqiong; Zhou, Hua; Dong, Qihan; Xu, Hongxi
Abstract: Quiescent cancer cells (QCCs), also known as dormant cancer cells, resist and survive chemo- and radiotherapy, resulting in treatment failure and later cancer recurrence when QCCs resume cell cycle progression. However, drugs selectively targeting QCCs are lacking. Saikosaponin A (SSA) derived from Bupleurum DC., is highly potent in eradicating multidrug-resistant prostate QCCs compared with proliferative prostate cancer cells. By further exacerbating the already increased autophagy through inactivation of Akt-mTOR signaling, SSA triggered cell death in QCCs. Contrarily, inhibition of autophagy or activation of Akt signaling pathway prevented SSA-induced cell death. The multicycle of Docetaxel treatments increased the proportion of QCCs, whereas administering SSA at intervals of Docetaxel treatments aggravated cell death in vitro and led to tumor growth arrest and cell death in vivo . In conclusion, SSA is posed as a novel QCCs-eradicating agent by aggravating autophagy in QCCs. In combination with the current therapy, SSA has potential to improve treatment effectiveness and to prevent cancer recurrence. Highlights: Saikosaponin A induces quiescent cancer cell death by further exacerbating autophagy. Saikosaponin A exacerbates autophagy through inactivation of Akt-mTOR signaling. Saikosaponin A enhances chemotherapeutic efficacy of Docetaxel in vitro and in vivo. Saikosaponin A-induced autophagy is essential for apoptosis occurrence. Saikosaponin A has potential to prevent treatment failure and cancer recurrence.